2021
DOI: 10.3390/nu13114167
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Pattern and Periodontitis—A Cross-Sectional Study

Abstract: The aim of the study was to investigate the relationship between specific known dietary patterns and the prevalence of periodontal disease in a northern population-based cohort study. We evaluated data from 6209 participants of the Hamburg City Health Study (HCHS). The HCHS is a prospective cohort study and is registered at ClinicalTrial.gov (NCT03934957). Dietary intake was assessed with the food frequency questionnaire (FFQ2). Periodontal examination included probing depth, gingival recession, plaque index, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 39 publications
4
37
0
Order By: Relevance
“…Our group recently investigated the MedD in a 6-week randomized clinical trial and found comparable results to the studies above [ 13 ]. The findings of that study were in accordance with a cross-sectional study that reported lower odds of periodontitis when the participants adhered to the MedD [ 14 ]. Accordingly, the MedD offers advantages both for general and oral health and should therefore be recommended to dental patients.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our group recently investigated the MedD in a 6-week randomized clinical trial and found comparable results to the studies above [ 13 ]. The findings of that study were in accordance with a cross-sectional study that reported lower odds of periodontitis when the participants adhered to the MedD [ 14 ]. Accordingly, the MedD offers advantages both for general and oral health and should therefore be recommended to dental patients.…”
Section: Introductionsupporting
confidence: 89%
“…Our results confirm the findings of Altun et al (2021). In their cross-sectional study, they found a lower risk for periodontal disease when adherence to the MedD was increased, and they used the MEDAS as an evaluation tool [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we found that women had a higher DASH score, whereas men were twice as often assigned the “low” DASH category. The same was found in an analysis of periodontitis [ 22 ]. Higher adherence to the DASH or the MEDAS diet was associated with less conventional cardiovascular risk factors and the prevalence of MetS.…”
Section: Discussionsupporting
confidence: 81%
“…An important recommendation combining the prevention of PD and ASCVD is to recommend a healthy diet. As indicated by Altun et al, the use of DASH diet/Mediterranean diet reduced the risk of PD (OR = 0.92; 95% CI: 0.87–0.97, p < 0.001 and OR = 0.93; 95% CI: 0.91–0.96, p < 0.001, respectively) [ 156 ]. These diets are also effective and recommended in the prevention of ASCVD [ 154 ].…”
Section: Discussionmentioning
confidence: 99%